Ethanol extract of Schisandrae chinensis fructus ameliorates the extent of experimentally induced atherosclerosis in rats by increasing antioxidant capacity and improving endothelial dysfunction - Xiu Chen; Jiahong Cao; Yong Sun; Yaolan Dai; Jiali Zhu; Xuemei Zhang; Xiaoqin Zhao; Liwen Wang; Tingting Zhao; Yongbiao Li; Youping Liu; Guihua Wei; et al. (Taylor & Francis Group, 2018)
Context: Schisandrae chinensis fructus, the dried ripe fruit of Schisandra chinensis (Turcz.) Baill. (Magnoliaceae) has been used for thousands of years as a traditional Chinese herb, which can attenuate and prevent the development of cardiovascular events. Objective: To evaluate the effects of the ethanol extracts from Schisandrae chinensis fructus fruit (EESC) on experimental atherosclerosis (AS) in rats. Materials and methods: Treatment with EESC (0.35, 0.7, 1.4 g/kg/d, i.g.) and simvastatin (4 mg/kg/d, i.g.) on AS rats for 3 weeks. Sprague-Dawley rats on normal chow and under water treatment were used as control. The content of schisandrin, schisandrin A and schisandrin B in EESC was detected by HPLC. Aortic pathology changes, serum biochemical indices and nuclear factor E2-related factor 2 (Nrf-2) and heame oxygenase-1 (HO-1) expressions were measured. Results: Schisandrin, schisandrin A and schisandrin B contents were 291.8, 81.46 and 279.1 mg/g of dry weight, respectively. EESC significantly reduced the aortic plaque area (76.5, 90.5 and 73.9% reduction), regulated the levels of serum lipid (p < 0.05), enhanced the antioxidant enzyme activities (p < 0.01), reduced the malondialdehyde levels (72.5, 69.3, 67.3%), and up-regulated the Nrf-2 and HO-1 expression (p < 0.05). Furthermore, EESC reduced the levels of oxidized-LDL and endothelin-1 and thromboxane B2 but increased that of 6-keto prostaglandin F1α (p < 0.05). Acute toxicity was calculated on mice to be LD50 > 20 g/kg. Conclusions: EESC positively affects the treatment of AS in vivo and the findings will provide a reliable theoretical basis for developing novel therapeutics.